Microsoft SQL Server 2012 bible - Jorgensen, Adam (Bible, 2012)
Chapter 5: SQL Server Management and Development Tools; Organizing the Interface; Registered Servers; Object Explorer; Using the Query Editor; Using the Solution Explorer; Getting a Jumpstart on Code with Templates and Code Snippets; Summary; Part II: Building Databases and Working with Data; Chapter 6: Introducing Basic Query Flow; Understanding Query Flow; FROM Clause Data Sources; WHERE Conditions; (0 row(s) affected)Columns, Stars, Aliases, and Expressions; Ordering the Result Set; Select Distinct; TOP (); Summary.